2017
DOI: 10.5812/jjm.60947
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Helicobacter pylori Virulence Related Genes (hpa and babA2) in Iranian Patients with Gastrointestinal Disorders

Abstract: Background: The clinical result severity of Helicobacter pylori infection is determined by a combination of environmental factors, host genetic background, and H. pylori virulence factors. A number of genes containing vacA, iceA, babA2, cagA, cagE, hsp60-70, and hpa have been identified to enhance H. pylori pathogenicity by encoding virulent proteins. The babA and hpa proteins are considered 2 major adhesion molecules, and thus they are key agents in the initial step of H. pylori invasion. Objectives: This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The area of each square represents the magnitude of association, and the horizontal tips of the diamond represent the 95% CI [56,57]. It was showed that babA2 as a virulence marker could predict clinical outcome, which was dependent on the geographic origin of the H. pylori strains [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The area of each square represents the magnitude of association, and the horizontal tips of the diamond represent the 95% CI [56,57]. It was showed that babA2 as a virulence marker could predict clinical outcome, which was dependent on the geographic origin of the H. pylori strains [27].…”
Section: Discussionmentioning
confidence: 99%
“…The sequence of the three babA gene alleles have been identified (babA1, babA2 and babB), but only the babA2 is involve d in Lewis-b binding activity. To date, several studies have evaluated the effect of H. pylori babA2 gene on risk of GC [19,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], but the results are conflicting possibly due to small sample size of single studies. In the present study, we conducted a meta-analysis to assess the association between H. pylori babA2 gene and GC risk based on published cases-control studies.…”
Section: Introductionmentioning
confidence: 99%
“…There were 20 studies [19,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] (Figure 3).…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
“…Furthermore, interaction between host's immunological defenses and H pylori virulence factors may play an important role in the development of GC [56,57]. It was showed that babA2 as a virulence marker could predict clinical outcome, which was dependent on the geographic origin of the H. pylori strains [27].…”
Section: The Increased Gc Risk Was Also Associated With Co-expressionmentioning
confidence: 99%
See 1 more Smart Citation